Developing English Instructional Materials for Young Learners Oriented to Left and Right Brain Accommodation - Berutu, Nursah Nola; Margana, Margana (Journal of Languages and Language Teaching, 2023)
The development and formulation of English language learning materials, meticulously tailored to encompass the cognitive processes of both the left and right brain hemispheres, emerge as a matter of profound import in the realm of promoting efficacious language acquisition among Junior High School students. In light of this imperative, the present research endeavors to construct and design English instructional materials with a distinct focus on seventh-grade learners within the Junior High School milieu, with an overarching objective of optimizing left- and right-brain accommodation. The research methodology employed is Research and Development (R&D). The procedural trajectory encompassed writing a syllabus, designing the materials, doing material evaluation, and revising the material draft. In the context of data collection, a twofold approach was undertaken, featuring targeted questionnaires designed to elicit data pertaining to both the students' instructional requisites and their perceived learning needs. This validation is derived from a tripartite evaluation, encompassing data analysis, expert assessment, and student feedback. Expert judgment, indicative of the materials' categorization as falling within the "good" bracket, substantiates the meticulous development process, with an average score of 3.8. Likewise, the evaluation, reflected in an average score of 3.13, corroborates the materials' efficacy in cultivating a conducive learning environment. In summation, this study epitomizes a deliberate and comprehensive endeavor to forge English instructional materials that transcend conventional paradigms by cognizantly accommodating the cognitive dimensions of learners' brains. The harmonious fusion of pedagogical design and cognitive insight, as evinced in the development and evaluation process, advocates for a dynamic shift in instructional material construction to better align with the multifaceted cognitive attributes of students in Junior High Schools.